Motivational climate and attitudes towards doping among Kenyan endurance runners - Kipchumba, K. K.; Rintaugu, E. G.; Mwangi, F. M. (Scientific Journal of Sport and Performance, 2022)
Doping is a worldwide problem that harms athletes' health and undermines the spirit of sport. Studies have shown that male athletes are more prone to doping than female athletes. Athletes with mastery climate have been associated with anti-doping attitudes, while those with performance climate have pro-doping attitudes. However, it is unclear whether motivational climate is equally important to attitude towards doping for males and females. Data were collected from 323 runners in Elgeyo-Marakwet County, Kenya, using cross-sectional survey design. Runners self-reported their motivational climate using Perceived Motivational Climate in Sport Questionnaire and attitudes towards doping using Performance Enhancement Attitude Scale. Correlational analysis indicated significant inverse relationship between mastery climate and doping attitude (rho = -.242; p < .001) and significant positive correlation between performance climate and doping attitude, (rho = .362; p < .001). Hierarchical regression analysis revealed performance and mastery climate were significant predictors of attitudes towards doping (F (3, 319) = 28.24, p = .001), and gender did not moderate the relations between motivational climate and doping attitudes (ß = -.028, p = .621). MANOVA results showed male athletes were significantly lower in performance climate scores (p = .045) and non-significantly low in mastery climate scores (p =.075) and doping attitude scores (p = .595) than females. In conclusion, performance climate was associated with doping attitudes in females- but not in males. Therefore, policy frameworks that buttresses the aspects of mastery climate as opposed to performance climate in females is likely to promote anti-doping attitudes.